Systemic antifungal prophylaxis for very low birthweight infants: a systematic review. Issue 3 (3rd September 2007) - Clerihew, L; Austin, N; McGuire, W
Abstract : Systematic review and meta-analysis of four randomised controlled trials suggest that prophylactic fluconazole reduces the incidence of invasive fungal infection in very low birthweight infants. Further trials are needed to provide more precise estimates of effect size, and to assess the effect on mortality, neurodevelopment and the emergence of antifungal resistance.